Factibilidad de realizar un examen clínico objetivo y estructurado en la carrera de Fonoaudiología - Díaz S., Mario; Arancibia S., Claudia; Bozzo N., Sergio (Revista Hospital Clínico Universidad de Chile, 2013)
Introduction: To evaluate clinical competences in medical education, objective structured clinical examination (OSCE) is a useful tool. Aims: The main objective was to evaluate the feasibility and usefulness of this activity for Phonoaudiology’s students. Material and methods: 52 second level phonoaudiology’s students participated in OSCE, which had 5 stations with simulated neurological patients and 6 stations for video and figures analysis. Evaluators were in an adjoining room, no visible to student, they filled a check list with the station objectives. Each station was designed to identify common neurological diseases that affect the language or swallowing of patients. Students had five minutes to solve the problem in each station. Results: Most students were able to recognize neurological disorders in both types stations. Mean rate performance in simulated stations was 63,41 +/- 11,38 %, and in not simulated stations was 56,92 +/-16,39%. Moreover, 97,8 +/- 2,7% of students declarated in accord with this activity. Discussion: The OSCE is feasible to be applied for phonoaudiology´s students. The activity allowed assess different clinical competences, knowledge and was well received by students.